Synthesis on Bio Reaction Kinetics of Biodiesel Production from Rubber Seed Oil Using Lipase as the Catalyst - Siti Norhaslina, Halim (2013)
Energy is fundamental to the quality of life on the earth. Meeting the growing demand for energy sustainably is one of the major challenges of the 21st century. The number of human also continuously grows bigger, causing energy request become higher. That is why our energy such as petroleum depleting very fast. The situation has led to the search for an alternative source of energy. The purpose of this study is to study on bio reaction kinetics of biodiesel production from rubber seed oil using lipase as the catalyst. Biodiesel is an alternative fuel that produced by chemical reaction of vegetable oil or animal fat with an alcohol which used for diesel engines. Biodiesel have advantages to use as a renewable energy like fossil fuel such as it is non toxic, biodegradable and greenhouse gas neutral. Biodiesel produced by using transesterification process. Transesterification process is triglycerides react with methanol and aid of catalyst produce methyl ester and glycerol as by product. In this study, we only focus the biodiesel production using enzymatic process. In this process, catalyst that will use is lipase Pseudomonas cepacia (P. Cepacia). The process optimization consisted of (a) Alcohol to oil molar ratio, (b) Catalyst amount, (c) Reaction temperature, and (d) Reaction time. 1H NMR spectrum of the RSO and biodiesel samples are analysed which confirms the conversion of RSO to biodiesel. The biodiesel properties have been investigated and are found to be comparable with diesel.